Molybdenum Disorder in Hydrated Sedovite, Ideally U(MoO4)2·nH2O, a Microporous Nanocrystalline Mineral Characterized by Three-Dimensional Electron Diffraction, Density Functional Theory Computations, and Complexity Analysis - Steciuk, Gwladys; Kiefer, Boris; Hornfeck, Wolfgang; Kasatkin, Anatoly V; Plášil, Jakub (Inorganic chemistry, 2021)
Sedovite, U4+(Mo6+O4)2·nH2O, is reported as being one of the earliest supergene minerals formed of the secondary zone. The difficulty of isolating enough pure material limits studies to techniques that can access the nanoscale combined with theoretical analyses. The crystal structure of sedovite has been solved and refined using the dynamical approach from three-dimensional electron diffraction data collected on natural nanocrystals found among iriginite. At 100 K, sedovite is monoclinic a ≈ 6.96 Å, b ≈ 9.07 Å, c ≈ 12.27 Å, and V ≈ 775 Å3 with space group C2/c. The microporous structure presents a characteristic framework built from uranium polyhedra and disordered Mo pyramids creating pore hosting water molecules. To confirm the formula U4+(Mo6+O4)2·nH2O, the possible presence of a hydroxyl group that would promote Mo5+ was tested with density functional theory (DFT) computations at the ambient temperature. DFT predicts that sedovite is a ferromagnetic insulator with a fundamental bandgap of Eg ∼ 1.7 eV with its chemical and physical properties dominated by U4+ rather than Mo6+. The structural complexity, IG,tot, of sedovite was evaluated in order to get indirect information about the missing formation conditions.Sedovite, U4+(Mo6+O4)2·nH2O, is reported as being one of the earliest supergene minerals formed of the secondary zone. The difficulty of isolating enough pure material limits studies to techniques that can access the nanoscale combined with theoretical analyses. The crystal structure of sedovite has been solved and refined using the dynamical approach from three-dimensional electron diffraction data collected on natural nanocrystals found among iriginite. At 100 K, sedovite is monoclinic a ≈ 6.96 Å, b ≈ 9.07 Å, c ≈ 12.27 Å, and V ≈ 775 Å3 with space group C2/c. The microporous structure presents a characteristic framework built from uranium polyhedra and disordered Mo pyramids creating pore hosting water molecules. To confirm the formula U4+(Mo6+O4)2·nH2O, the possible presence of a hydroxyl group that would promote Mo5+ was tested with density functional theory (DFT) computations at the ambient temperature. DFT predicts that sedovite is a ferromagnetic insulator with a fundamental bandgap of Eg ∼ 1.7 eV with its chemical and physical properties dominated by U4+ rather than Mo6+. The structural complexity, IG,tot, of sedovite was evaluated in order to get indirect information about the missing formation conditions.